Factors Affecting Educational Motivation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the factors affecting students' motivation in the educational process and its specific features. Educational motivation is a special type of motivation included in educational activities. In a broader sense, educational motivation can be viewed as a general name for processes, methods, and means of encouraging students to engage in effective cognitive activity and actively assimilate the content of education.